(untitled) (Research, Society and Development, 2024)
The prevalence of myopia is increasing globally, and the presence of high myopia increases the risk of developing permanent visual impairments that could be avoided. Access to appropriate refractive correction and methods of preventing and controlling myopia progression are effective measures to prevent such vision impairment. The objective of this article is to present the results on the use of spectacle lenses with Defocus Incorporated Multiple Segments (DIMS) technology, with the purpose of evaluating the effectiveness of these lenses for correcting and controlling the progression of myopia in children and adolescents, aged 6 to 18 years when compared to single vision (SV) lenses. An integrative review of the literature was carried out in which clinical trials were included, published between 2018 and March 2024 in the PubMed and Virtual Health Library databases, which evaluated the effects of DIMS lenses in relation to SV lenses to control progression of myopia, with participants aged between 6 and 18 years. In short, 5 studies were included that fit the eligibility criteria and the scope of the research. The parameters used for comparative analysis were the variation in the spherical equivalent of refraction and the axial length during the use of the assigned treatment. From these, it was found that the SV lenses did not demonstrate a myopia-retardant effect, while the DIMS lenses were effective for this function, thus revealing the effectiveness of peripheral myopic defocus in the retina to control the progression of myopia.